2018
DOI: 10.1007/s13193-018-0740-z
|View full text |Cite
|
Sign up to set email alerts
|

The Results of the Combine Treatment of Patients with Liver Bilobar Metastases from Colorectal Cancer Using Radiofrequency Ablation

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide. The mortality from CRC remains very high. The main cause of such a high mortality is a disseminate process with the appearance of distant metastases. In this regard, the treatment of metastatic lesions is recognized as an important trend in modern oncology. The program of study included 176 patients with colorectal cancer after primary tumor removal with the malignant progression-multiple (more than 4) bilobar liver metastases. The research was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In the field of gastric cancer, hepatectomy for liver metastases may be acceptable if the patient has a small number of metastases and no factors indicating unresectability [33][34][35]. The usefulness of RFA has been documented for liver metastasis of colorectal cancer [36][37][38][39], and RFA may be an alternative to hepatectomy in patients with gastric cancer [40][41][42][43]. RFA seemed to be effective in our patient (Case 3).…”
Section: Discussionmentioning
confidence: 78%
“…In the field of gastric cancer, hepatectomy for liver metastases may be acceptable if the patient has a small number of metastases and no factors indicating unresectability [33][34][35]. The usefulness of RFA has been documented for liver metastasis of colorectal cancer [36][37][38][39], and RFA may be an alternative to hepatectomy in patients with gastric cancer [40][41][42][43]. RFA seemed to be effective in our patient (Case 3).…”
Section: Discussionmentioning
confidence: 78%
“…Yang et al conducted a study including CRLM and reported that RFA with chemotherapy prolonged the median OS (29 vs. 12 months, p = 0.002) compared to chemotherapy alone [ 43 ]. A retrospective study by Kaganov et al included 176 patients with colorectal cancer with 824 liver metastases; 98 and 78 of whom underwent RFA with chemotherapy and chemotherapy-alone, respectively [ 44 ]. In the RFA with chemotherapy and chemotherapy-alone groups, the 1-, 2-, and 3-year OS were 73.5% and 39.6%, 25.1% and 6.3%, and 7.2% and 2.1%, respectively, and the median OS was 18 and 11 months, respectively [ 44 ].…”
Section: Effect Of Ablative Therapy In Combination With Chemotherapy ...mentioning
confidence: 99%
“…A retrospective study by Kaganov et al included 176 patients with colorectal cancer with 824 liver metastases; 98 and 78 of whom underwent RFA with chemotherapy and chemotherapy-alone, respectively [ 44 ]. In the RFA with chemotherapy and chemotherapy-alone groups, the 1-, 2-, and 3-year OS were 73.5% and 39.6%, 25.1% and 6.3%, and 7.2% and 2.1%, respectively, and the median OS was 18 and 11 months, respectively [ 44 ]. The OS was significantly better in the RFA with chemotherapy group than in the chemotherapy-alone group [ 44 ].…”
Section: Effect Of Ablative Therapy In Combination With Chemotherapy ...mentioning
confidence: 99%
See 1 more Smart Citation